METHOD OF DEVELOPING COGNITIVE INTEREST IN STUDENTS WHEN TEACHING ENGINEERING AND COMPUTER GRAPHICS - Boymuratov Farrukh Khamzayevich (American Journals, 2025)
This article analyzes the methodology for developing students' cognitive interest in teaching engineering and computer graphics. The psychological and pedagogical foundations of cognitive interest are studied, and innovative pedagogical methods, technologies, and approaches for the effective organization of this process are considered. Particular attention is paid to the role of interactive learning, problem-based approaches, gamification, and group assignments in increasing students' interest. These methods are aimed at strengthening students' knowledge and preparing them for future professional activities. The article also provides practical recommendations for teachers and analyzes the practical results of developing cognitive interest. In conclusion, recommendations and methodological approaches are proposed aimed at improving the educational system.
Keywords: cognitive interest, engineering and computer graphics, pedagogical methods, interactive learning, problem-based approach, student motivation, innovative pedagogy, educational process, gamification, practical results, recommendations for teachers.